Encyclopedia of atmospheric sciences - North, Gerald R.; Pyle, J. C.; Zhang, Fuqing, 1969- (Academic Press, 2015)
Encyclopedia of Atmospheric Sciences, 2nd Edition is an authoritative resource covering all aspects of atmospheric sciences, including both theory and applications. With more than 320 articles and 1,600 figures and photographs, this revised version of the award-winning first edition offers comprehensive coverage of this important field. The six volumes in this set contain broad-ranging articles on topics such as atmospheric chemistry, biogeochemical cycles, boundary layers, clouds, general circulation, global change, mesoscale meteorology, ozone, radar, satellite remote sensing, and weather p.